Zarīnī sānge: da Puṣhto da hunarī adab dolūnah - Rafīʻ, Habīb Allāh (Da Afghānistān da ʻUlūmo Akāḍemī, da Zhabo aw Adabiyāto ʻIlmī aw Taḥqīī Markaz, Puṣhto Tolạnah)
On various forms of Pushto songs and prose literature.